(untitled) (Journal of Enam Medical College, 2012)
Primary pulmonary hypertension (PPH) is a rare disease which usually presents with shortness of breath. We report a case of a female patient who presented with dyspnoea. We diagnosed her as a case of PPH on the basis of detailed history, careful physical examination and common investigations like electrocardiogram (ECG), chest radiography and Doppler echocardiograhy. DOI: http://dx.doi.org/10.3329/jemc.v1i2.11468 J Enam Med Col 2011; 1(2): 81-84